Using Deliberative Pedagogy as a Tool for Critical Thinking and Career Preparation Among Undergraduate Public Health Students - Nelson-Hurwitz, Denise C.; Buchthal, Opal Vanessa (Frontiers in Public Health, 2019)
Engagement of undergraduate public health students in active learning pedagogy has been identified as critical for recruitment, retention, and career preparation efforts. One such tool for engagement that has proven successful in STEM programs is deliberative pedagogy, where it is used to stimulate student interest in research and policy applications of technical course content. Broadly applied, deliberative pedagogy is a consensus model of decision-making, applied as an in-class exercise, where students work in small groups and model a community task force with assigned group roles. In these groups, students collect evidence from literature and media sources, and prepare a consensus response to an assigned question. Here we present an adaptation of this pedagogy to provide undergraduates with the tools needed to actively engage in public health policy and planning work groups. This adaptation is first applied during an introductory public health course, where it is used as a tool for engagement and excitement, and as a critical thinking exercise. It additionally serves as an opportunity for students to apply information literacy skills and engage with research and policy initiatives discussed in class. The same tool is reintroduced prior to graduation in a capstone course, where the emphasis shifts to application of research skills and analytical concepts. The activity is also an opportunity for students to apply professional skills needed for engagement in program development, program evaluation, institutional policy, and legislative advocacy. Through application of this pedagogical tool at two critical time points in an undergraduate curriculum, students develop skills necessary for early career professionals and are better prepared to actively engage in policy and planning as it relates to critical public health initiatives, both locally and globally.